Formative Assessment of Social-Emotional Skills Using Rubrics: A Review of Knowns and Unknowns - Pancorbo, Gina; Primi, Ricardo; John, Oliver P.; Santos, Daniel; De Fruyt, Filip (Frontiers in Education, 2021)
Educational practitioners have been increasingly interested in the use of formative assessment and rubrics to develop social-emotional skills in children and adolescents. Although social-emotional rubrics are nowadays commonly used, a thorough evaluation of their psychometric properties has not been conducted. In this non-exhaustive review, we examine the knowns and unknowns of the use of formative assessment approaches and rubrics in social-emotional learning. We first review initiatives of formative assessment and development of rubrics to assess social-emotional skills. Then, we discuss challenges associated with the development and use of rubrics to evaluate social-emotional skills in youth focusing on (i) assessment of single skills versus assessment of a comprehensive taxonomy of skills; (ii) developing rubrics' performance level descriptions that accurately describe increasing mastery of skills; (iii) obtaining adequate internal consistency and discriminant validity evidence; (iv) self-reports versus observer reports of skills; and finally (v) how to account for adolescents' development in the construction of rubrics. This review outlines a research agenda for the psychometric study of rubrics to be used in social-emotional skill assessment.